2012
DOI: 10.1016/j.forpol.2012.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Carbon sequestration and uneven-aged management of loblolly pine stands in the Southern USA: A joint optimization approach

Abstract: and Agribusiness for their comments and suggestions to improve the thesis quality. I would also like to thank Dr. Quang V. Cao for his practical guidance and suggestions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…As C markets gain stature, determining the qualities of C pricing mechanisms sufficient to shift forest management towards C sequestration is an increasing priority. (23) Carbon prices have shown instability in some markets, (24) and the creation of broader-reaching C pricing schemes could shift management toward greater C sequestration as the price of C increases. (25) However, variability in the price of C makes the utility of C trading schemes to improve forest management for increased C storage difficult to predict.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As C markets gain stature, determining the qualities of C pricing mechanisms sufficient to shift forest management towards C sequestration is an increasing priority. (23) Carbon prices have shown instability in some markets, (24) and the creation of broader-reaching C pricing schemes could shift management toward greater C sequestration as the price of C increases. (25) However, variability in the price of C makes the utility of C trading schemes to improve forest management for increased C storage difficult to predict.…”
Section: Introductionmentioning
confidence: 99%
“…(25) However, variability in the price of C makes the utility of C trading schemes to improve forest management for increased C storage difficult to predict. (26) For example, increasing C prices were insufficient to promote alternative lower-harvest management in Pinus taeda L. forests, (23) though Murray (27) found increasing C prices would increase rotation length in simulated Douglas-fir stands. Some carbon markets minimize price uncertainty and associated financial risk, such as the California cap-and-trade system's price floor starting at $10 per carbon credit.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple-benefit forestry economic models are less frequent for uneven-aged stands, even though uneven forest structures are recognized for their biological, hydrological and aesthetic benefits [19]. Some exceptions include the use of uneven-aged forest management models to analyze the economic implications of maintaining certain levels of tree biodiversity [9,19,20], or the integration of carbon benefits into forest management decisions [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…While most models attempt to circumvent the dynamic complexities of optimizing uneven-aged management 1 , Haight (1985) and Haight and Getz (1987) specify and numerically compute a theoretically sound dynamic optimization model for uneven-aged management. In another line of research, Chang (1981) and Chang and Gadow (2010) study optimal partial cutting cycles and growing stocks in uneven-aged stands, while Parajuli and Chang (2012) extend the model with carbon sequestration. Recently it has been shown that both clearcut and continuous cover management can be covered by a single framework (Tahvonen 2015(Tahvonen , 2016.…”
Section: Introductionmentioning
confidence: 99%